trình bày lại câu m
`(-6)/7 + 2/3 + 4/7 `
`= ( (-6)/7 + 4/7 ) + 2/3 `
`= - 2/7 + 2/3 `
`= (-6+14)/21 = 8/21`
\(a)\dfrac{-3}{5}+\dfrac{1}{5} =\dfrac{-3+1}{5} =\dfrac{-2}{5}\)
\(b)\dfrac{1}{8}+\dfrac{-2}{3} =\dfrac{3}{24}+\dfrac{-16}{24} =\dfrac{3-16}{24} =\dfrac{-13}{24}\)
\(c)\dfrac{-4}{7}+\dfrac{-5}{2} =\dfrac{-8}{14}+\dfrac{-35}{14} =\dfrac{-8-35}{14} =\dfrac{-43}{14}\)
\(d)\dfrac{-4}{3}-\dfrac{2}{3} =\dfrac{-4-2}{3} =\dfrac{-6}{3} =-2\)
\(e)\dfrac{-5}{6}-\dfrac{-1}{3} =\dfrac{-5}{6}-\dfrac{-2}{6} =\dfrac{-5+2}{6} =\dfrac{-3}{6} =\dfrac{-1}{2}\)
\(f)\dfrac{7}{9}-\dfrac{-5}{8} =\dfrac{56}{72}-\dfrac{-45}{72} =\dfrac{56+45}{72} =\dfrac{101}{72}\)
\(g)\dfrac{-8}{9}.\dfrac{3}{2} =\dfrac{-8.3}{9.2} =\dfrac{-24}{18} =\dfrac{-4}{3}\)
\(h)\dfrac{-15}{6}:\dfrac{-7}{3} =\dfrac{-15}{6}.\dfrac{3}{-7} =\dfrac{-15.3}{6.(-7)} =\dfrac{15}{14}\)
\(k)\dfrac{12}{15}:\dfrac{-3}{-4} =\dfrac{12}{15}.\dfrac{-4}{-3} =\dfrac{12.(-4)}{15.(-3)} =\dfrac{16}{15}\)
\(m)\dfrac{-6}{7}+\dfrac{2}{3}+\dfrac{4}{7} =\dfrac{-18}{21}+\dfrac{14}{21}+\dfrac{12}{21} =\dfrac{-18+14+12}{21} =\dfrac{8}{21}\)
\(n)\dfrac{5}{9}+\dfrac{-4}{5}+\dfrac{-5}{9}+\dfrac{2}{5} =(\dfrac{5}{9}+\dfrac{-5}{9})+(\dfrac{-4}{5}+\dfrac{2}{5}) =(\dfrac{-5+5}{9})+(\dfrac{-4+2}{5}) =0+\dfrac{-2}{5} =\dfrac{-2}{5} \)
\(o)\dfrac{3}{-10}-\dfrac{-4}{9}+\dfrac{-11}{10} =(\dfrac{3}{-10}+\dfrac{-11}{10})-\dfrac{-4}{9} =(\dfrac{-3-11}{10})-\dfrac{-4}{9} =\dfrac{-14}{10}-\dfrac{-4}{9} =\dfrac{-126}{90}-\dfrac{-40}{90} =\dfrac{-126+40}{90} =\dfrac{-86}{90} =\dfrac{-43}{45} \)
\(p)\dfrac{13}{7}.\dfrac{-4}{5}+\dfrac{13}{7}.\dfrac{-3}{2} =\dfrac{13}{7}.(\dfrac{-4}{5}+\dfrac{-3}{2}) =\dfrac{13}{7}.(\dfrac{-8-15}{10}) =\dfrac{13}{7}.\dfrac{-23}{10} =\dfrac{13.(-23)}{7.10} =\dfrac{-299}{70}\)
\(q)\dfrac{4}{7}.\dfrac{-12}{25}+\dfrac{-12}{25}.\dfrac{-3}{14} =\dfrac{-12}{25}.(\dfrac{4}{7}+\dfrac{-3}{4}) =\dfrac{-12}{25}.(\dfrac{16-21}{28}) =\dfrac{-12}{25}.\dfrac{-5}{28} =\dfrac{-12.(-5)}{25.28} =\dfrac{60}{700} =\dfrac{3}{35}\)
\(q)\dfrac{4}{7}.\dfrac{-12}{25}+\dfrac{-12}{25}.\dfrac{-3}{14} =\dfrac{-12}{25}.(\dfrac{4}{7}+\dfrac{-3}{14}) =\dfrac{-12}{25}.\dfrac{-5}{14} =\dfrac{-6}{35}\)